2001
DOI: 10.2134/agronj2001.933495x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Subsoil Nitrogen by Alfalfa, Alfalfa–Wheat, and Perennial Grass Systems

Abstract: The role of alfalfa (Medicago sativa L.) in extracting NO3–N from deep soils of areas with cold, short growing seasons, such as western Canada, is not well understood. A study was established in 1990 to determine NO3–N extraction ability to 300 cm; initial soil NO3–N concentrations were high (>8 mg kg−1). Systems included continuous alfalfa; annual rotations of spring wheat (Triticum aestivum L.), field pea (Pisum sativum L.), and barley (Hordeum vulgare L.); a native‐grass system [big bluestem (Andropogon ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
(61 reference statements)
3
31
1
Order By: Relevance
“…Compared with annual crops which extracted nitrate-N only from 0-120 cm soil depth, alfalfa extracted significant amounts of nitrate-N to 270 cm soil depth (Entz et al 2001). Peterson and Russelle (1991) reported that alfalfa can absorb nutrients from depths of 11 m. However, Campbell et al (1994) and Voorhees and Holt (1969) stated that the depth of significant nutrient extraction by alfalfa was approximately 2.5 m. Nutrients present in the sub-soil may thus be used by taproot plants and become available in surface soil after crop residues are returned to the soil.…”
Section: Introductionmentioning
confidence: 90%
“…Compared with annual crops which extracted nitrate-N only from 0-120 cm soil depth, alfalfa extracted significant amounts of nitrate-N to 270 cm soil depth (Entz et al 2001). Peterson and Russelle (1991) reported that alfalfa can absorb nutrients from depths of 11 m. However, Campbell et al (1994) and Voorhees and Holt (1969) stated that the depth of significant nutrient extraction by alfalfa was approximately 2.5 m. Nutrients present in the sub-soil may thus be used by taproot plants and become available in surface soil after crop residues are returned to the soil.…”
Section: Introductionmentioning
confidence: 90%
“…These findings suggest that frequent summer fallow can cause large accumulation of NO 3 -N in soil and occasional heavy rains in relatively dry regions can result in downward movement of NO 3 -N deep into the soil profile. To minimize NO 3 -N leaching problem, it is suggested that producers should reduce or even eliminate summer fallow (especially tilled) by increasing cropping frequency using no-tillage (Campbell et al 1984;Guillard et al 1995;Zentner et al 2001), proper crop rotations to include perennial grasses with deep/ extensive rooting system and high N requirements (Olsen et al 1970;Entz et al 2001) or cover crops (Vos et al 1998). However, quantitative information is needed on the actual contribution of increased cropping frequency using no-tillage and inclusion of deep-rooted perennial and annual crops in rotations in minimizing NO 3 -N accumulation and leaching in the soil profiles.…”
Section: Hydrologymentioning
confidence: 99%
“…to more shallow-rooted grass species (Entz et al 2001). It also has a higher optimum temperature for growth than cool-season grasses.…”
mentioning
confidence: 99%
“…As perennial pastures begin using soil moisture as soon as green-up occurs in the spring (Twerdoff et al 1999), they frequently have utilized almost all-available soil moisture by late summer (Twerdoff et al 1999;Bradshaw 2007). In addition to the decreasing soil water, air temperatures in the southern prairies during the JulyÁ August period can exceed 308C, which exacerbates slow growth resulting in early dormancy of cool-season grasses (Frank et al 1996;Baron and Belanger 2007).…”
mentioning
confidence: 99%